Transmission line matrix (TLM) modeling of self-heating in power PIN diodes. (September 2018) - Mimouni, S.; Saidane, A.; Chalabi, D.; Abboun-Abid, M.
Abstract: Design of high-performance electronic components with stable static and dynamic characteristics requires a study of self-heating on electrical properties. TLM method is used to model electrothermal behavior of PIN diodes. Simulation results show a non-uniform temperature distribution in the device. TLM simulation results are in good agreement with those obtained by DESSIS-ISE commercial simulator. TLM computational effort is only a fraction of that required by finite element methods. TLM method is useful in dealing with nonlinear problems since it is unconditionally stable. Modeling and analysis results show that device self heating depends very much on material physical parameters and its geometry. In addition, it has been observed that blocking and conduction times influence heat dissipation. Graphical abstract: Highlights: It is essential to evaluate heat distribution in each area of the PIN diode to properly design the device. This study uses one-dimensional (1D) TLM method to analyze electro thermal behavior of PIN diode. It highlights self-heating under switching and its influence on turn-on and turn-off transients. TMax variation as a function of applied reverse voltage pulse durations for different N + substrate thicknesses is studied. TLM model is validated using results found with a commercial finite element simulator DESSIS-ISE.